The food and beverage home delivery service and the market purchasing behavior due to the impact of covid_19 - Salazar Duque, Diego (2020)
This article main contribution is to analyze customer’s purchasing behavior in Quito city about food and beverage home delivery service after the lockdown generated by COVID-19. Its purpose allows understanding, from gender and age, how the marketing stimuli influence in buyer’s decision; this will allow food and beverage sector to implement strategies that allow achieving business objectives and maintaining itself over time. Quantitative descriptive research has been considered for this study through a structured questionnaire.  The principal results obtained were that delivery home buyers prefer food based on chicken, which is acquired by telephone, being Facebook the channel that influences the most their decision. The conclusion reached in the study is that there is a significant difference opinion in both ages and gender where digital platforms play an important role in purchase of home delivery service.